GAMBARAN ATTACHMENT DAN INDIVIDUATION PADA INDIVIDU TUNA RUNGU - Clara Moningka; Laura Kartina (Psibernetika, 2011)
Humans are social animals that often form the interaction with others and strive to maintain these interactions. In an interaction, individuals try to establish intimacy or often referred to as an attachment. This does not necessarily occur in every interaction. Attachment security, trust, and happiness in individuals. Individuals will feel accepted by others. On the other hand, in addition to developing attachment with others, individuals also should be able to develop independent behavior. Individuals provide space or distance between himself and others. He does not always depend on the presence of others. This is called individuation. This study aims to see the picture of attachment and individuation in deaf individuals. Deaf individuals have difficulty communicating because of limitations in the hearing. In general, individuals with limited float flavor hard to believe, or even otherwise very dependent on others. In this study the attachment and individuation in deaf individuals were measured using a scale of fear of attachment (FA) and the fear of individuation (FI) from Kaplan. Research conducted on 66 people deaf. The validity of measuring instruments is .324 - .623 to .247 gauge and the FA - .555 to .786 and FI with the reliability of .709. Based on the results of measurement is known that the empirical mean score higher than average scores on both the theoretical aspects of the measure. This indicates that these individuals tend to be afraid of an intimate relationship with another person. On the one hand they are also dependent on other people when you've found someone who is used as a dependent. Keywords : attachment, individuation, individu tuna rungu